Rapport annuel - registre belge des maladies neuromusculaires 2015 - Corinne Bleyenheuft; Viviane Van Casteren (WIV-ISP, 2017)
The goals of the Belgian neuromuscular diseases registry are to enable epidemiological research to evaluate the importance of the diseases and the patient characteristics, to provide information to the public health authorities for planning of health care in Belgium, to promote health services for patients having a neuromuscular disease and to improve recruitment for clinical trials. The patients’ recruitment increases every year since the registry’s creation in 2008. In 2015, a total number of 4670 patients were registered. The particularity of a registry dedicated to neuromuscular disorders (compared to other health care registries) is that the patients’ population is heterogeneous. Neuromuscular disorders comprise indeed different rare diseases affecting the peripheral nerves, or the muscles, or the neuromuscular junction, or anterior horn cells. Some of those diseases are genetic, while others are not. The vast majority of them are degenerative, and sometimes result in death in the short or in the long term. Some of those diseases occur during the childhood, and others occur during the adulthood. It is thus difficult to give a general overview of such a heterogeneous group of patients. General demographic data show a slightly higher number of males than females (N = 2610 versus N = 2043). The patients’ recruitment is currently better in the north than in the south of the country. This is presumably due to the geographical repartition of the reference centers collecting the data. Nevertheless, the gap between those two regions tends to decrease year after year. 152 deaths occurred in 2015. Amongst them, 96 occurred in patients suffering from amyotrophic lateral sclerosis. For the year 2015, the ten most prevalent diseases in the registry are: hereditary motor and sensory neuropathy, myotonic dystrophy type 1, amyotrophic lateral sclerosis, Duchenne muscular dystrophy, hereditary spastic paraplegia, limb girdle muscular dystrophy, chronic inflammatory demyelinating polyneuropathy, facioscapulohumeral dystrophy, spinocerebellar ataxias, and postpolio syndrome. Those ten diseases are more specifically analyzed in the present report. The registry also collects specific data relative to the international “TREAT-NMD” network, for two defined groups of diseases: Duchenne and Becker muscular dystrophies, and spinal muscular atrophies. Those specific data are also analyzed in the present report. The procedure for entry of data was assessed during this data collection. 5% of the registered files were compared to the original patient file in every reference center. The results show that some centers should improve the quality of the registration process. In the future, some of the data may directly be registered by the patient through a tablet in the waiting room.
Keywords: BNMDR; Maladies neuromusculaires; registre